Atherosclerosis in the single-cell era. Issue 5 (October 2018) - Winkels, Holger; Ehinger, Erik; Ghosheh, Yanal; Wolf, Dennis; Ley, Klaus
Abstract : Purpose of review: The immune system plays a critical role in the development and modulation of atherosclerosis. New high-parameter technologies, including mass cytometry (CyTOF) and single-cell RNA sequencing (scRNAseq), allow for an encompassing analysis of immune cells. Unexplored marker combinations and transcriptomes can define new immune cell subsets and suggest their functions. Here, we review recent advances describing the immune cells in the artery wall of mice with and without atherosclerosis. We compare technologies and discuss limitations and advantages. Recent findings: Both CyTOF and scRNAseq on leukocytes from digested aortae show 10–30 immune cell subsets. Myeloid, T, B and natural killer cells were confirmed. Although cellular functions can be inferred from RNA-Seq data, some subsets cannot be identified based on current knowledge, suggesting they may be new cell types. CyTOF and scRNAseq each identified four B-cell subsets and three macrophage subsets in the atherosclerotic aorta. Limitations include cell death caused by enzymatic digestion and the limited depth of the scRNAseq transcriptomes. Summary: High-parameter methods are powerful tools for uncovering leukocyte diversity. CyTOF is currently more powerful at discerning leukocyte subsets in the atherosclerotic aorta, whereas scRNAseq provides more insight into their likely functions.